IMPACT OF DUST PARTICLES ON AIR QUALITY AND ASSOCIATED HUMAN HEALTH IN ILORIN NIGERIA (FUDMA JOURNAL OF SCIENCES, 2020)
To improve our understanding of the impact of desert dust on human health, there is need to constantly monitor and examined the dust related phenomena. Therefore, twenty 20 year’s (1998–2018) data of visibility for Ilorin Nigeria were used to estimate the concentrations of the Total Suspended Particles (TSP) and Particulate Matter PM10 as usually used to monitor air quality on international level. The results established the threshold for daily concentration of TSP (254) and PM10 (186) μgm−3 at the study sites. It also identified months (November-March) of the following year with the greatest number of days having low air quality (high concentration of TSP and PM10). These months are responsible for 47% of the annual air pollution and number of days above the US EPA-NAAQSTSP, US EPA-NAAQS PM10 as well as the 24-hour EU-LVAQ regulations, respectively. Furthermore, some considerable numbers of days were found to experienced hazardous atmospheric condition for the total number of days, Harmattan and summer respectively. The concentrations of PM10 (0-54 μgm−3) showed absence of good air quality throughout the period of study. Even though, there were significant number of days associated with moderate air quality most of which occurs during summer. Consequence of which can lead to increased respiratory symptoms and aggravation of lung diseases. It was also observed that, the concentrations of TSP and PM10 start of build up in the atmosphere by October, reaching peak in December and January before it decline by April and remain low with almost uniform values until September.
Keywords: Harmattan, Human health, Ilorin, Particulate matter, Summer